Comparative study on goat oocyte recovery methods and factors affecting the quantity and quality of oocytes - Abdullah, Ramli; Khadijah, W.E.W.; Anna, A.A.; Hisham, M.N. (2013)
A strategize step in oocyte recovery is important and beneficial in producing successful production of high-quality Cumulus Oocyte-Complexes (COC) for in vitro maturation, fertilization and culture (IVMFC), nuclear transfer and other emerging technologies. Experiments were conducted to compare Oocyte Recovery (OR) between Laparoscopic Ovum Pick-Up (LOPU) and ovarian slicing and to evaluate the effects of OR cycle, hormone stimulation, oestrus synchronization, breeds, liveweight and age of goats on the quantity and quality of oocytes obtained. In Experiment 1, oocytes were recovered from abattoir-derived ovaries by the slicing method. The ovaries were transported to the laboratory for immediate harvesting. The slicing method yielded significantly (p<0.05) larger number of oocytes per ovary than LOPU (22.53±2.78 vs. 6.10±0.46). However, the proportion of Grade A oocytes was highest from the LOPU technique (30.51±4.14) compared to the slicing method (19.07±3.57). LOPU resulted in good quality Cumulus Oocytes Complexes (COC) with more than 5 layers of cumulus cells. Experiment 2 consisted of three OR cycles (OR-1, OR-2 or OR-3); four durations of oestrus synchronization using CIDR (Day-10, -14, -17 or -21); three goat breeds (Boer Crossbred, Mixed breed or Katjang); 4 age groups (Young, Mature, Old or Very Old) and 4 levels of body weight (20, 21-29, 30-37 or 38 kg). Goats were synchronized using Control Internal Drug Release (CIDR) combined with 125 jig Estrumate and hyperstimulated with 70 mg FSH and 400 IU hCG after the removal of CIDR 24 h later. There was no significant effect of OR cycle, CIDR removal goat breed, age or body weight on the total number of oocytes recovered per ovary. Katjang goats yielded a higher proportion of Grade A oocytes compared to Boer Crossbreds and mixed breeds which had a higher proportion of Grade C oocytes (p<0.05). Age and weight of animals had no significant effect on the quality of oocytes recovered. Grade A and B oocytes were obtained in OR-1, whilst the repetition of LOPU resulted in an increment of Grade C oocytes in OR-2 and OR-3, respectively. Day-10 and -21 gave the highest cumulative percentage of 58 and 64% for Grade A and B oocytes, respectively. Under the conditions of the experiment, LOPU yielded better quality oocytes from the Katj ang goats using less or no OR repetition, with oestrus synchronization at 10 or 21-Day. © 2013 Academic Journals Inc.